2003
DOI: 10.1128/mcb.23.14.4901-4916.2003
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Increases the Decay of Matrix Metalloproteinase 9 mRNA by Inhibiting the Expression of mRNA-Stabilizing Factor HuR

Abstract: Dysregulation of extracellular matrix turnover is an important feature of many inflammatory processes. Rat renal mesangial cells express high levels of matrix metalloproteinase 9 (MMP-9) in response to inflammatory cytokines such as interleukin-1 beta. We demonstrate that NO does strongly destabilize MMP-9 mRNA, since different luciferase reporter gene constructs containing the MMP-9 3 untranslated region (UTR) displayed significant reduced luciferase activity in response to the presence of NO. Moreover, by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
3
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 70 publications
4
121
3
1
Order By: Relevance
“…Eberhardt and coauthors were the first who revealed the role of cis-regulatory AU-rich elements (ARE) in the 3′-untranslated region of MMP-9 mRNA in the regulation of mRNA stability. Their studies showed that mRNAstabilizing factor HuR and the presence of NO regulated MMP-9 mRNA stability [26,35]. In addition to AREs, we found other types of regulatory elements in the 3′-UTR, i.e., targets for miRNAs affecting efficiency of gene expression.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Eberhardt and coauthors were the first who revealed the role of cis-regulatory AU-rich elements (ARE) in the 3′-untranslated region of MMP-9 mRNA in the regulation of mRNA stability. Their studies showed that mRNAstabilizing factor HuR and the presence of NO regulated MMP-9 mRNA stability [26,35]. In addition to AREs, we found other types of regulatory elements in the 3′-UTR, i.e., targets for miRNAs affecting efficiency of gene expression.…”
Section: Discussionmentioning
confidence: 82%
“…The UTR446 fragment contains previously described AU-rich cis-regulatory elements (ARE, Fig. 1a) which target host mRNAs towards rapid degradation and therefore may affect the efficiency of MMP-9 expression [25,26]. We then asked whether UTR446 inhibitory properties that we observed could be explained exclusively by ARE inhibitory activity.…”
Section: ′-Utr Of Mmp-9 Contains Regulatory Elements Inhibiting Genementioning
confidence: 96%
“…There are a number of gene regulatory sequences driving the MMP-9 expression, with AP-1 and NF-jB being the most prominent [5]. Once produced, the MMP-9 mRNA is subjected to regulation at its stability level by nitric oxide (NO) [6]; as well it can apparently be translocated in neurons towards activated dendrites [7]. Notably, MMP-9 contains ARE-like sequences that have been suggested to be of pivotal importance for the translocation in other messages [8].…”
Section: Introductionmentioning
confidence: 99%
“…How does NO regulate Ras mRNA stability? NO can disrupt the stability of mRNA encoding other proteins, such as matrix metalloproteinase 9, by interfering with proteins that normally bind to AU-rich elements; AU elements are contained in the 3Ј untranslated region of ras (39). NO decreases steady-state levels of K-Ras and N-Ras but not H-Ras (Fig.…”
Section: Discussionmentioning
confidence: 99%